On The Double-Vacua Duality of Multi-Scalar Higgs and NGB-Dual Higgses in Scherk-Schwarz Breaking of 5-dimensional SU(6) Symmetry - Jusak Sali Kosasih; Andreas Hartanto; Laksana Tri Handoko; Freddy Permana Zen (Journal of Mathematical and Fundamental Sciences, 2014)
A special condition of Scherk-Schwarz and S^1/Z2 orbifold breaking brings about both a weakly-coupled SU(6) baby Higgs and a strongly-coupled will-be simplest little Higgs scalar in the near-brane of SU(3) x SU(3)x U(1). The latter produces SU(3) VEVs and simplest little-like Higgs after triplet-triplet splitting and, under quadratic-based and non-quadratic-based Coleman-Weinberg potential, the simplest little-like Higgs yields exotic Higgses, scalar-pair and 3-scalar Higgses in the so-called one-by-one and collective breakings. A generalized non-quadratic-based Coleman-Weinberg potential utilizing a NGB-like scalar produces NGB-dual Higgses with a squared mass relevant to the components of a 3-scalar Higgs that further create a duality of 3-scalar Higgs and NGB-dual Higgses. This is due to a double-vacua property such that each vacuum responds equally to the shifts happening at either non-zero or zero-VEV vacuum.